2013
DOI: 10.1515/hf-2012-0157
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wood durability on the suppressive effect of increased temperature on wood decay by the brown-rot fungus Postia placenta

Abstract: Local climate conditions have a major influence on the biological decomposition of wood. To examine the influence of different temperature regimes on wood decay caused by the brown rot fungus Postia placenta in wood with differing natural durability, sapwood (sW) and heartwood (hW) of Scots pine, inoculated mini-blocks were incubated for up to 10 weeks at temperatures conducive or above optimal to wood decay. We profiled mass loss (ML) and wood composition, and accompanying changes in wood colonization and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The extent of amplification was calculated as the mean of 2 replicates from each sample. The yield of P. placenta gDNA was adjusted in relation to the recovery rate of the pGEM reference DNA (Hietala et al 2014). The same trend was found for undiluted, 10-fold and 100-fold dilutions, but the 100-fold gave a slightly better yield and is presented in the results chapter.…”
Section: Qpcr Anlaysismentioning
confidence: 52%
See 1 more Smart Citation
“…The extent of amplification was calculated as the mean of 2 replicates from each sample. The yield of P. placenta gDNA was adjusted in relation to the recovery rate of the pGEM reference DNA (Hietala et al 2014). The same trend was found for undiluted, 10-fold and 100-fold dilutions, but the 100-fold gave a slightly better yield and is presented in the results chapter.…”
Section: Qpcr Anlaysismentioning
confidence: 52%
“…gDNA quantification has shown to be more sensitive than ergosterol and kition assays for estimation of fungal biomass in early stages of decay both in sterile laboratory samples (Eikenes et al 2005) and for field samples (Pilgård et al 2011). Hietala et al (2014) found that the suppressive effect of suboptimal temperature on wood decay caused by P. placenta appeared more pronounced in Scots pine heart wood than in sapwood. At 30°C heartwood showed no mass loss, poor substrate colonization (gDNA quantification) and marker gene transcript level profiles indicating a starvation situation.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it was concluded that the ACQ treatment was able to inhibit the effectiveness of the enzymes in some manner and that different resistant woods effected microbial colonisation Brought to you by | NIBIO -Norsk institutt for bioøkonomi Authenticated Download Date | 9/6/17 2:50 PM and enzyme activity differently during decay. Hietala et al (2014) found that the suppressive effect of suboptimal temperature on P. placenta decay appeared more pronounced in Scots pine heartwood with increased durability compared to Scots pine heartwood with low decay resistance. This was particularly pronounced for cultures incubated at 30°C.…”
Section: Introductionmentioning
confidence: 90%
“…Genomic DNA levels of P. placenta indicative of fungal biomass were quantified by quantitative polymerase chain reaction (qPCR) (Hietala et al 2014). Three biological replicates from the same board were pooled, resulting in six replicates (two replicates from each board) from each treatment and harvesting point.…”
Section: Introductionmentioning
confidence: 99%
“…Standard PCR cycling parameters, according to 7500 Real Time PCR System (Applied Biosystems, Foster City, CA, USA), were applied. The yield of fungal gDNA was adjusted in relation to the recovery rate of the pGEM reference DNA included to adjust for extractability of gDNA from the samples (Hietala et al 2014). The internal standard pGEM was quantified in a 25 μl PCR reaction with a 300 nM concentration of the forward primer CCCAGTCACGACGTTGTAAAACG, reverse primer TGTGTGGAATTGTGAGC GGA and the FAM-labelled TaqMan ® probe: (Applied Biosystems, Foster City, CA, USA) CACTATAGAATACTCAA-GCTTGCATGCCTGCA described by Coyne et al (2005).…”
Section: Introductionmentioning
confidence: 99%